Effects of high dose retinoic acid on TGF-?2 expression during pancreatic organogenesis - Colakoglu, Neriman; Kukner, Aysel; Oner, Jale; Sonmez, M. Fatih; Oner, Hakan; Ozan, Enver (Springer, 2005)
The aim of this study was to investigate the effects of excess all-trans retinoic acid, a vitamin A metabolite, on pancreatic organogenesis and TGF-beta 2 expression during prenatal development in rats. First group of animals used as control while a single dose of 60 mg/kg all-trans retinoic acid was ingested by the mothers, at day 8 of gestation (before the neurulation period) in group II and at day 12 of gestation (after the neurulation period) in group III, and all embryos were sacrificed at day 18 of gestation. TGF-beta 2 expression was detected in the capsule, acini and Langerhans islets in the control group. In the pancreas of group II, dilatation and congestion of interlobular vessels were observed. Langerhans islet structures were completely absent. Moreover acinar TGF-beta 2 immune reactivity was not determined. In group III, acinar expression of TGF-beta 2 in acid was similar to that in the controls but their Langerhans islets TGF-beta 2 immune reactivity was significantly less than the controls. In view of the present findings we suggest that TGF-beta 2 plays important role in pancreatic morphogenesis and administration of excess all-trans retinoic acid before neurulation inhibit TGF-beta 2 expression disrupted pancreatic morphogenesis particularly Langerhans islets. However, its administration after neurulation had less adverse affect on pancreatic organogenesis and TGF-beta 2 immune reactivity.
Keywords: pancreas; prenatal development; TGF-beta 2; immunohistochemistry